Molecularly imprinted electrochemical sensor for ochratoxin A detection in food samples - Pacheco, João G. (2015)
A novel electrochemical sensor for ochratoxin A (OTA) detection was fabricated through the modification of a glassy carbon electrode (GCE) with multiwalled carbon nanotubes (MWCNTs) and a molecularly imprinted polymer (MIP). The MWCNTs dramatically promoted the sensitivity of the developed sensor, while polypyrrole (PPy) imprinted with OTA served as the selective recognition element. The imprinted PPy film was prepared by electropolymerization of pyrrole in the presence of OTA as a template molecule via cyclic voltammetry (CV). The electrochemical oxidation of OTA at the developed sensor was investigated by CV and differential pulse voltammetry (DPV). The developed MIP/MWCNT/GCE sensor showed a linear relationship, when using DPV, between peak current intensity and OTA concentration in the range between 0.050 and 1.0 μM, with limits of detection (LOD) and quantification of 0.0041 μM (1.7 μg/L) and 0.014 μM (5.7 μg/L) respectively. With the developed sensor precise results were obtained; relative standard deviations of 4.2% and 7.5% in the evaluation of the repeatability and reproducibility, respectively. The MIP/MWCNT/GCE sensor is simple to fabricate and easy to use and was successfully applied to the determination of OTA in spiked beer and wine samples, with recoveries between 84 and 104%, without the need of a sample pre-treatment step.